2020
DOI: 10.1016/j.parepi.2020.e00182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malaria preventive education on the use of long-lasting insecticidal nets among pregnant females in a Teaching Hospital in Osun state, south-west Nigeria

Abstract: Background: Malaria in pregnancy is a major public health problem in Nigeria. Long-Lasting Insecticidal Nets (LLINs) have been advocated as an effective tool against malaria transmission. However, success of this intervention largely depends on the knowledge and practices regarding malaria and its prevention. Unfortunately, few studies have been done on effect of malaria preventive education on use of LLIN in pregnancy. Objective: To assess the knowledge of malaria and determine the effect of malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Pregnant women who recognize that malaria poses a risk to their fetuses are 3.25 times more likely to use LLINs than their counterparts. This theory is confirmed by a study conducted in Pakistan, which found that women utilize LLINs more if their prior pregnancy resulted in a neonatal death (26).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Pregnant women who recognize that malaria poses a risk to their fetuses are 3.25 times more likely to use LLINs than their counterparts. This theory is confirmed by a study conducted in Pakistan, which found that women utilize LLINs more if their prior pregnancy resulted in a neonatal death (26).…”
Section: Discussionmentioning
confidence: 55%
“…The likelihood of LLIN use was 4.4 times higher among pregnant women who had LLIN use information than among pregnant women who did not have information. This idea is also evidenced by the study conducted on the effect of malaria preventive education on the use of LLINs among pregnant women in Nigeria ( 27 ).…”
Section: Discussionmentioning
confidence: 81%
“…Malaria morbidity and death have been demonstrated to be reduced when ITNs are used alone [12]. The Roll Back Malaria (RBM) alliance, on the other hand, advocates using intermittent preventative treatment (IPT) also in areas where malaria transmission is steady to reduce the disease's burden among pregnant women [13,14]. In many malaria-endemic regions of Sub-Saharan Africa, the execution of the IPTp policy has been plagued by periodic shortages of the program medicine, denying pregnant women on prenatal consultations access to the treatment [15,16].…”
Section: Discussionmentioning
confidence: 99%